SPIRITUALITAS IGNASIAN SEBAGAI JALAN MEMBANGUN KESATUAN HIDUP BERKELUARGA: SEBUAH STUDI KASUS KUALITATIF - Susanto, Gabriel Abdi (Sanata Dharma University, 2025)
This article examines Ignatian Spirituality as a spiritual framework capable of fostering and sustaining unity in family life amid differences in character, cultural background, and life values. Departing from the reality of conflicts commonly encountered in contemporary families, the study argues that spirituality functions not merely as a reinforcement of faith but as a transformative force in relational life. Employing a qualitative approach through a case study method, this research focuses on a Catholic married couple who have lived their marital vocation for more than five decades. The primary data consist of personal reflective documents, which are thematically analyzed in light of the principles of Saint Ignatius of Loyola’s Spiritual Exercises. The findings demonstrate that key practices of Ignatian Spirituality—such as self-denial, discernment of spirits, freedom from disordered attachments, magnanimity, and humility—play a significant role in managing conflict, deepening mutual understanding, and nurturing relational unity within the family. Concrete practices, including reflective prayer, shared spiritual exercises, open communication, and the courage to undergo personal transformation, emerge as effective pathways for relational healing and growth. This article concludes that Ignatian Spirituality is not merely a personal devotional practice but a holistic and effective approach to building sustainable family unity. By orienting family life toward Christ as its ultimate end, Ignatian Spirituality offers a concrete spiritual resource for families to grow in love, interior freedom, and faithful commitment.